2017
DOI: 10.7554/elife.26057
|View full text |Cite
|
Sign up to set email alerts
|

A large gene family in fission yeast encodes spore killers that subvert Mendel’s law

Abstract: Spore killers in fungi are selfish genetic elements that distort Mendelian segregation in their favor. It remains unclear how many species harbor them and how diverse their mechanisms are. Here, we discover two spore killers from a natural isolate of the fission yeast Schizosaccharomyces pombe. Both killers belong to the previously uncharacterized wtf gene family with 25 members in the reference genome. These two killers act in strain-background-independent and genome-location-independent manners to perturb th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
241
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(274 citation statements)
references
References 68 publications
21
241
0
Order By: Relevance
“…Additionally, Hu et al, 2017 also identified two different wtf drivers in another Sp isolate (CBS5557) and both have a potential alternate start codon in exon 2. Of the 25 wtf loci in Sp , four ( wtf4 , wtf13 , wtf19 and wtf23 ) also appear to be capable of encoding two proteins and we predict these are active drive genes.…”
Section: Resultsmentioning
confidence: 92%
“…Additionally, Hu et al, 2017 also identified two different wtf drivers in another Sp isolate (CBS5557) and both have a potential alternate start codon in exon 2. Of the 25 wtf loci in Sp , four ( wtf4 , wtf13 , wtf19 and wtf23 ) also appear to be capable of encoding two proteins and we predict these are active drive genes.…”
Section: Resultsmentioning
confidence: 92%
“…Hu et al found that gamete killing meiotic drive also contributed to infertility in the laboratory S. pombe /CBS5557 hybrids. They also identified two meiotic drive loci on chromosome 3 of CBS5557 (Hu et al, ).…”
Section: Discovery Of Meiotic Drive In Fission Yeastmentioning
confidence: 99%
“…Both groups identified distinct meiotic drive genes that are members of the previously uncharacterized wtf gene family. The S. kambucha genes were named wtf4 and wtf28 , whereas the CBS5557 genes were called cw9 and cw27 (Hu et al, ; Nuckolls et al, ). The wtf gene family owes its catchy name to the family's association with long terminal repeats (LTRs) of the Tf transposons (with Tf transposon).…”
Section: Discovery Of Meiotic Drive In Fission Yeastmentioning
confidence: 99%
See 2 more Smart Citations